PROSES LITERASI DIGITAL TERHADAP ANAK: Tantangan Pendidikan di Zaman Now - Mustofa Mustofa; B. Heni Budiwati (IAIN Ponorogo, 2019)
Abstact: Digital Literacy Process for Children: Educational Challenges in the Age of Now. The method used in writing this article is the study of literature. Digital literacy is an important pillar for the future of education. Digital literacy is a knowledge base, which is supported by integrated information technology. The purpose of writing this article is to know the important elements in digital literacy and the digital literacy process for children. Nine important elements in the world of digital literacy, namely: Social Networking, Transliteracy, Maintaining Privacy, Managing Digital Identity, Creating Content, Organizing and Sharing Content, Reusing / repurposing Content, Filtering and Selecting Content. Self Broadcasting. Digital literacy process for children through several stages, namely: 1) Digital literacy movement in the family, 2) Digital literacy in the school literacy movement, 2) Digital literacy movement in the community. Abstrak: Proses Literasi Digital Terhadap: Tantangan Pendidikan di Zaman Now. Artikel ini ditulis dengan metode study literarure. Literasi digital merupakan basic pengetahuan yang disupport oleh tekonologi informasi yang saling terhubung. Penulisan artikel ini memiliki tujuan yaitu untuk memahami bagian-bagian penting dalam literasi digital dan prosedur literasi terhadap anak. Sembilan bagian dalam dunia literasi digital, yaitu social networking, transliterasy, maintaining privasi, managing digital identity, creating content, organizing and sharing content, reusing/repurposing content, filtering and selecting content, self broadcasting. Proses literasi digital terhadap anak memalui beberapa tahapan, yaitu: 1) gerakan literasi digital di dalam keluarga 2) literasi digital dalam gerakan literasi sekolah 3) gerakan literasi digital di dalam masyarakat.